Implementasi Metode Scrum Pada Sistem Informasi Penjualan Dengan Fitur Live Chat Menggunakan Framework Codeigniter (Studi Kasus : Puppies Station) - Azizah Azzahra; Alvino Octaviano (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Sales information system is one of the systems used for business management by managing data related to sales. The sales information system can disseminate product information, purchase, sale and manage business data. Sales information system related to e-commerce. E-commerce makes it easier for customers to find product information. In addition, the live chat feature in e-commerce will make it easier for customers to find information by communicating with sellers. The author uses primary data and secondary data in this study. The system development method in this study uses the scrum method while the methodology used in this study is a qualitative descriptive method by analyzing how sales are made by Puppies Station to its customers. With this sales information system, it is hoped that it can help Puppies Station in communicating with customers and managing sales to make it easier and increase.